2016
DOI: 10.1108/cr-03-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral lessons from Flipkart’s Big-Billion Day sale

Abstract: Purpose The purpose of this paper is to understand the behavioral lessons and managerial implications of deep discount strategies used by e-commerce firms to gain a competitive advantage over rivals. The paper seeks to understand the behavioral aspects of consumer and competitor response to such online sales, particularly with reference to e-satisfaction and e-loyalty. The case study seeks to: understand the behavioral aspects of utility and customer satisfaction; understand the behavioral aspects influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Bronnenberg and Wathieu (1996), Briesch et al (1997), Mazumdar and Papatla (2000), Erdem et al (2001), Han et al (2001), Kivetz et al (2004), Moon et al (2006), Terui and Dahana (2006), Pauwels et al (2007), Newman and Newman (2007), Habib and Miller (2009), Masiero and Hensher (2010), Ataman and Rooderkerk (2010), Rose and Masiero (2010), Delle Site and Filippi (2011), Nicolau (2011), Neumann et al (2012), Koppalle et al (2012), Dayaratna and Kannan (2012) and Hu et al (2012) have found robust empirical support for the asymmetric effect of price increases and decreases, and for loss aversion. Jayakumar (2016) documented behavioral lessons from Flipkart’s Big-Billion Day sale in India and recommended that e-tailers should use the principles of behavioral economics, including framing effects, reference price and principles of loss aversion to influence customer decision-making in their favor.…”
Section: Integrated Review Analysis and Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Bronnenberg and Wathieu (1996), Briesch et al (1997), Mazumdar and Papatla (2000), Erdem et al (2001), Han et al (2001), Kivetz et al (2004), Moon et al (2006), Terui and Dahana (2006), Pauwels et al (2007), Newman and Newman (2007), Habib and Miller (2009), Masiero and Hensher (2010), Ataman and Rooderkerk (2010), Rose and Masiero (2010), Delle Site and Filippi (2011), Nicolau (2011), Neumann et al (2012), Koppalle et al (2012), Dayaratna and Kannan (2012) and Hu et al (2012) have found robust empirical support for the asymmetric effect of price increases and decreases, and for loss aversion. Jayakumar (2016) documented behavioral lessons from Flipkart’s Big-Billion Day sale in India and recommended that e-tailers should use the principles of behavioral economics, including framing effects, reference price and principles of loss aversion to influence customer decision-making in their favor.…”
Section: Integrated Review Analysis and Synthesismentioning
confidence: 99%
“…, Rose and Masiero (2010), DelleSite and Filippi (2011), Nicolau (2011), Neumann et al (2012,Koppalle et al (2012),Dayaratna and Kannan (2012) andHu et al (2012) have found robust empirical support for the asymmetric effect of price increases and decreases, and for loss aversion Jayakumar (2016). documented behavioral lessons from Flipkart's Big-Billion Day sale in India and recommended that e-tailers should use the principles of behavioral…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Influence of internet marketing management has often been the main concern (Agnihotri et al, 2016;Jayakumar, 2016;Srinivasan and Moorman, 2005). IT-enabled customer management is crucial for customer satisfaction and online business sales success (Jayakumar, 2016).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Influence of internet marketing management has often been the main concern (Agnihotri et al, 2016;Jayakumar, 2016;Srinivasan and Moorman, 2005). IT-enabled customer management is crucial for customer satisfaction and online business sales success (Jayakumar, 2016). Since the start of public use of the internet in the early 1990s, this technology has been popularized and widely adopted as the core of globalization for firms to interact with their clients and other internal and external stakeholders, with the purpose of transforming social relations' resources into corporate sales (Agnihotri et al, 2016;Zhao and Wu, 2014).…”
Section: Conceptual Modelmentioning
confidence: 99%